Why We Need Better Reporters to Solve Our Security Problems. Issue 6 (3rd June 2017) - Cohen, Fred
Abstract: I do not go to the media when I find out confidential information that I wish the world would understand. Instead, I write articles about the underlying issues we face and how I think they might be reasonably solved. And when the media occasionally seeks to talk to me about such issues, I tell them what I think but nothing specific about clients. That's all part of my job, and I try to do it well. The job of the media is to seek the truth and tell all of us about it. But the media in the United States seems to be so weak at seeking the truth that I am starting to understand why people seek them out to leak secrets. Unless you lead them by the nose to the thing that stinks, they do not seem to have the nose for news that they once did have.